Stability of Intraocular Lens With Different Haptic Design: A Swept-Source Optical Coherence Tomography Study - Xiao, Zixuan; Wang, Geng; Zhen, Miaoru; Zhao, Zifeng (Frontiers in Medicine, 2021)
Purpose: To investigate the stability of intraocular lens (IOLs) with different haptics by swept-source anterior-segment optical coherence tomography (AS-OCT). Methods: Sixty-eight eyes from 55 patients received the implantation of Rayner 920H (Closed C-loop Group), Zeiss 509M (Plate Group) or Lenstec SOFTEC HD (C-loop Group) IOLs. The tilt and decentration of IOLs were evaluated using AS-OCT at least 1 month postoperatively. Results: Mean decentration and tilt of IOLs were 0.18±0.12 mm (range 0.02 to 0.59 mm) and 5.63±1.65˚ (range 2.2˚ to 9.6˚) respectively. Decentration was significantly smaller in the plate haptic group (0.12±0.06 mm) as compared to the C-loop group (0.22±0.13 mm, P = 0.02). The tilt of IOL was also significantly smaller in the plate haptic group (4.96±0.89˚) as compared to the C-loop group (6.28±1.83˚, P = 0.01). There was marginal difference between the Closed C-loop group (5.52±1.74˚) and C-loop group (6.28±1.83˚, P = 0.07). Conclusions: The Plate-haptic IOLs should have better stability for the decentration and tilt than the C-loop design IOLs.